Reverse Dynamization Accelerates Bone-Healing in a Large-Animal Osteotomy Model. (3rd February 2021) - Glatt, Vaida; Samchukov, Mikhail; Cherkashin, Alexander; Iobst, Christopher
Abstract : Background: Reverse dynamization is a mechanical manipulation regimen designed to accelerate bone-healing and remodeling. It is based on the hypothesis that a fracture that is initially stabilized less rigidly allows micromotion to encourage initial cartilaginous callus formation. Once substantial callus has formed, the stabilization should then be converted to a rigid configuration to prevent the disruption of neovascularization. The aim of the present study was to investigate whether bone-healing can be accelerated using a regimen of reverse dynamization in a large-animal osteotomy model. Methods: Transverse 2-mm tibial osteotomies were created in 18 goats, stabilized using circular external fixation, and divided into groups of 6 goats each: static fixation (rigid fixation), dynamic fixation (continuous micromotion using dynamizers), and reverse dynamization (initial micromotion using dynamizers followed by rigid fixation at 3 weeks postoperatively). Healing was assessed with the use of radiographs, micro-computed tomography, and mechanical testing. Results: Radiographic evaluation showed earlier and more robust callus formation in the dynamic fixation and reverse dynamization groups compared with the static fixation group. After 8 weeks of treatment, the reverse dynamization group had reduced callus size, less bone volume, higher bone mineral density, and no evidence of radiolucent lines compared with the static fixation and dynamic fixation groups. This appearance is characteristic of advanced remodeling, returning closest to the values of intact bone. Moreover, the tibiae in the reverse dynamization group were significantly stronger in torsion compared with those in the static fixation and dynamic fixation groups. Conclusions: These findings confirmed that tibial osteotomies under reverse dynamization healed faster, healed objectively better, and were considerably stronger, all suggesting an accelerated healing and remodeling process. Clinical Relevance: This study demonstrates that the concept of reverse dynamization challenges the current understanding regarding the optimal fixation stability necessary to maximize the regenerative capacity of bone-healing. When reverse dynamization is employed in the clinical setting, it may be able to improve the treatment of fractures by reducing the time to union and potentially lowering the risk of delayed union and nonunion.